2006
DOI: 10.1021/jp060588h
|View full text |Cite
|
Sign up to set email alerts
|

Observation of pH-Dependent Back-Electron-Transfer Dynamics in Alizarin/TiO2 Adsorbates:  Importance of Trap States

Abstract: The dependence of the interfacial electron transfer in alizarin-sensitized TiO2 nanoparticles on the sample pH has been examined via transient absorbance spectroscopy in the visible spectral region (443-763 nm). Excitation of the alizarin/TiO2 system with visible pump pulses (lambdaexc = 500 nm) leads to a very fast electron injection (tauinj < 100 fs) over a wide pH range. Back electron transfer shows complicated multiphasic kinetics and strongly depends on the acidity of the solution. The strong dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
90
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 56 publications
12
90
2
Order By: Relevance
“…[12,19,[22][23][24] The system consisting of the organic dye alizarin and TiO 2 is characterized by a strong electronic coupling. Theoretical [30] and experimental [21,25,27] approaches showed that the excited state of alizarin is close to the conduction band edge of TiO 2 , a position with a reduced density of acceptor states, which makes this system an interesting candidate for investigations on interfacial ET. Despite the relative position of the alizarin excited state and the conduction band edge of TiO 2 , the FET is not less efficient than that from dyes with an excited state well above the conduction band edge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,19,[22][23][24] The system consisting of the organic dye alizarin and TiO 2 is characterized by a strong electronic coupling. Theoretical [30] and experimental [21,25,27] approaches showed that the excited state of alizarin is close to the conduction band edge of TiO 2 , a position with a reduced density of acceptor states, which makes this system an interesting candidate for investigations on interfacial ET. Despite the relative position of the alizarin excited state and the conduction band edge of TiO 2 , the FET is not less efficient than that from dyes with an excited state well above the conduction band edge.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] The importance of these trap states for the BET dynamics in the dyesensitized TiO 2 nanoparticles was shown earlier by our group. [21,27] The great surface-to-volume ratio of semiconductor nanoparticles ensures a highly efficient coupling of dye molecules. However, this high surface-to-volume ratio also leads to a high density of trap states, which inevitably influences the BET kinetics in these dye-sensitized semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…In such devices, the photoinduced electron-transfer (ET) reactions at the dye-semiconductor interface, in particular the processes of electron injection from an electronically excited state of a chemisorbed dye molecule into the semiconductor substrate, represent a key step for photonic energy conversion [33][34][35][36][37][38] . In recent years, photoinduced ET processes in dye-semiconductor systems have been studied in great detail experimentally with femtosecond spectroscopy techniques 34,35,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] . It has been shown that electron-injection processes at the dye-semiconductor interfaces often take place on an ultrafast sub-picosecond timescale 37,43,45,46,57,58 .…”
Section: Introductionmentioning
confidence: 99%
“…[12,22,23] The fast electron injection (< 100 fs) from photoexcited alizarin directly to the surface state of the TiO 2 colloid has also been observed in alkaline (pH 9) aqueous solution. [24] The injected electrons in the dye-sensitized solar cell then travel through TiO 2 nanoporous film to the collecting contact or may recombine with the dye cation [back electron transfer (BET)]. Widespread BET dynamics on a timescale of femtoseconds up to microseconds has been observed [18,[25][26][27] and the variability of BET is normally explained by strong contributions of semiconductor effects such as charge trapping and spatial diffusion, which is strongly defined by the presence of the trapping states.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast dynamics in such a system was investigated by femtosecond time-resolved spectroscopy in the UV/Vis and mid-IR spectral regions. We used the dye alizarin, which is well known as a suitable electron donor, [12,13,24] as a sensitizer (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%